(1E)-1-(2-pyrazinyl)ethanone thiosemicarbazone (PT) as a tyrosinase inhibitor with anti-browning activity: Spectroscopy, DFT and molecular docking studies - Syamimi Sulfiza, Shamsuri; Erna Normaya, .; Hakimah, Ismail; Anwar, Iqbal; Mohd Bijarimi, Mat Piah; Yang Farina, .; Ahmad Sazali, Hamzah; Mohamad Norazmi, Ahmad (Elsevier Ltd, 2023)
In this study, (1E)-1-(2-Pyrazinyl)ethanone thiosemicarbazone (PT) was synthesized and characterized using Fourier-transform infrared (FTIR), ultraviolet-visible (UV–Vis), proton nuclear magnetic resonance (1HNMR ) and carbon-13 nuclear magnetic resonance (13CNMR ) spectroscopy. The vibrational frequencies were analysed using the Vibrational Energy Distribution Analysis (VEDA) program. The chemical properties of PT, including electron density distribution and intramolecular interactions, were characterized using in-silico methods based on Mulliken atomic charges, molecular electrostatic potential (MEP), quantum theory of atoms in molecules and reduced density gradient noncovalent interaction approaches. PT exhibits a significant inhibitory effect on enzymatic browning (6 and 24 h) and tyrosinase enzymes (IC50 = 7.75 μM). Kinetic analysis shows that PT is a mixed-type inhibitor, with respective Km and Vmax values of 0.632 mM and 0.0044 μM/s, and that it forms a reversible enzyme-inhibitor interaction. The PT-tyrosinase interaction was experimentally evaluated based on 1D, second derivatives of 1D, 2D and 3D IR spectroscopy. Furthermore, analysis of absorption, distribution, metabolism, excretions and toxicity properties revealed good physicochemical properties of PT according to the drug scores and Lipinski's Rule of Five. Lastly, the mechanisms of PT against tyrosinase were visualized and supported by means of a molecular docking approach.